2012
DOI: 10.1049/iet-ipr.2012.0196
|View full text |Cite
|
Sign up to set email alerts
|

Colour demosaicking with directional filtering and weighting

Abstract: Digital cameras usually use a single sensor covered with a colour filter array which samples only one colour at the location of each pixel. Restoring a full-colour image by the demosaicking technique is a key task in the digital imaging pipeline. This study proposes a novel demosaicking approach based on the existing directional filtering and weighting techniques. The contributions of this study are two-fold. First, the authors analyse the advantages and limitations of the existing directional filtering and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…We compare the performance of the suggested EBD algorithm with five state of the art algorithms: DDFW [6], DLMMSE [5], LU [3], AHD [7] and NAT [4]. MATLAB code was kindly provided by authors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We compare the performance of the suggested EBD algorithm with five state of the art algorithms: DDFW [6], DLMMSE [5], LU [3], AHD [7] and NAT [4]. MATLAB code was kindly provided by authors.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [1] surveyed recent demosaicing algorithms and broadly classified them as either spatial-domain [3,4,5,6,7,8] or frequency-domain approaches [9,10]. Li et al showed that even the current state of the art algorithms tend to produce artifacts at high saturated edges and varying hue areas.…”
Section: Introductionmentioning
confidence: 99%
“…Digital imaging devices find a broad range of applications, particularly in digital cameras, surveillance devices, and mobile phones [1][2][3][4][5]. Every pixel must consist of three independent primary color components: red, green, and blue, when a digital camera obtains a color image [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the cost, currently available digital cameras uses color filter array (CFA) to obtain a color image. Therefore, each pixel only captures one color, and this process is mosaicking, and the opposite process is demosaicking (or color interpolation) [7][8][9]. The opposite process stands for reconstructing missing two colors information.…”
Section: Introductionmentioning
confidence: 99%